Adenomatoid Tumor of Epididymis-A Case Report - Mallik, Ashraf Uddin; Rahman, Md Mostafizur; Karmaker, Uttam; Ferdous, Baikali (KYAMC Journal, 2018)
Adenomatoid tumor is a very rare benign tumor of mesothelial origin. It is very difficult to distinguish carcinoma from an adenomatoid tumor. This is a report of a case of an adenomatoid tumor of the right epididymis of a man of 38-year-old who came to Urology OPD with pain and palpable swelling on the right testis. He also complaints of severe burning during ejaculation. We diagnose the case by ultrasonogram (USG) and Fine Needle Aspiration Cytology (FNAC). Right epididymectomy has done and histopathology revealed adenomatoid tumor. As the tumor is very rare, the case is to report for its clinical entity. KYAMC Journal Vol. 9, No.-3, October 2018, Page 141-143